When are projections also embeddings? - Moroz, I; Letellier, C; Gilmore, R (2007)
We study an autonomous four-dimensional dynamical system used to model certain geophysical processes. This system generates a chaotic attractor that is strongly contracting, with four Lyapunov exponents lambdai that satisfy lambda1+lambda2+lambda3<0 , so the Lyapunov dimension is DL=2+|lambda3|/lambda1<3 in the range of coupling parameter values studied. As a result, it should be possible to find three-dimensional spaces in which the attractors can be embedded so that topological analyses can be carried out to determine which stretching and squeezing mechanisms generate chaotic behavior. We study mappings into R3 to determine which can be used as embeddings to reconstruct the dynamics. We find dramatically different behavior in the two simplest mappings: projections from R4 to R3 . In one case the one-parameter family of attractors studied remains topologically unchanged for all coupling parameter values. In the other case, during an intermediate range of parameter values the projection undergoes self-intersections, while the embedded attractors at the two ends of this range are topologically mirror images of each other.